Mitigating Seafood Waste Through a Bycatch Donation Program - Watson, Jordan T.; Stram, Diana L.; Harmon, Jim (Frontiers in Marine Science, 2020)
Discarding of prohibited, under-sized, or nontarget finfish is a major problem globally. Many such unwanted or banned catches do not survive long enough to be released alive, creating complex ecological and policy issues for the fishing industry. In U.S. Federal waters, regulation requires bycatch to be avoided as practicable and bycatch of some finfish species is designated as prohibited species catch (PSC). By regulation, PSC cannot be retained or sold and it must be returned to the sea (dead or alive). Some PSC species have strict limits to further incentivize their avoidance and limit bycatch mortality and these limits can lead to fishery closures. Despite extensive efforts to avoid bycatch in the U.S. and elsewhere, unwanted catches still occur, creating the potential for substantial food waste. We present one rarely discussed approach to maximize the value of dead, unwanted or prohibited finfish catches. The Prohibited Species Donation (PSD) program utilizes trawl fishery PSC that would otherwise be discarded by instead donating it to hunger relief organizations. This program simultaneously provides food and reduces waste while avoiding inadvertent incentives for catching prohibited species. For 26 years, the non-profit organization, SeaShare, has worked with the Alaska seafood industry to distribute 2660 t (~23.5 million servings) of prohibited species donations (salmon and halibut), high quality seafood that would have otherwise been discarded due to prohibition on retention. The PSD program provides an example that addresses food security and social value, an under-represented perspective in the global dialogue on unwanted catches.